Electrosurgery in Gastrointestinal Endoscopy: Bench to Bedside - Nabi, Zaheer; Lopez, Priscilla; Reddy, D. Nageshwar (Journal of Digestive Endoscopy, 2024)
Electrosurgical generator units (ESUs) are instrumental in modern therapeutic gastrointestinal (GI) endoscopy, converting household alternating current into high-frequency current to generate thermal energy within tissues. This review elucidates the essentials of electrosurgery, exploring the thermal effects on tissue, current resistance, voltage, current density, duty cycle, crest factor, and the distinctions between monopolar and bipolar circuitry. The concept of duty cycle, the proportion of time electrical current is delivered, and crest factor, the ratio of peak to root mean square voltage, are essential while comparing differently named modes across various commercially available ESUs. This article discusses the practical applications of electrosurgery in therapeutic GI endoscopy procedures, including endoscopic sphincterotomy, polypectomy, endoscopic mucosal resection, endoscopic submucosal dissection, and peroral endoscopic myotomy. It outlines recommended modes and settings for ESUs across various procedures, emphasizing the balance between cutting and coagulation to achieve optimal outcomes while minimizing adverse effects. The review further addresses special considerations for the use of grounding pads and the management of patients with implanted cardiac devices during electrosurgical procedures. This article concludes with a call for a deeper understanding of electrosurgical principles and their application in GI endoscopy to ensure patient safety and procedural success, backed by references to relevant literature and detailed tables summarizing electrosurgical modes and settings for various therapeutic interventions.
Keywords: electrosurgery; endoscopy; cutting; coagulation; polypectomy; endoscopic resection